Developing a euro area accounting matrix: issues and applications - Tjeerd Jellema; Steven Keuning; Peter McAdam; Reimund Mink (European Central Bank (ECB), 2004)
Abstract: An important part of external or policy shocks is transmitted throughout the economy via various channels of transactions. To analyse such channels and to predict the impact of shocks, it is expedient to know who recently exchanged what with whom and for what purpose. The most appropriate format for presenting intersectoral linkages at the national level is in a National Accounting Matrix (NAM). A NAM is defined as the presentation of a sequence of integrated accounts and balancing items in a matrix that elaborates the linkages between a supply and use table and institutional sector accounts. This paper compiles the first pilot Euro Area Accounting Matrix (EAAM) and considers its usefulness for the euro area's economic analysis. It also reports on the solution of a number of aggregation and consolidation issues that arise when constructing a multi-country accounting matrix.
Keywords: E00; E19; 330; euro area; National Accounting Matrix; National Accounts